Cost-Driven strategies in consumer food behavior during global economic turmoil - evidence from Taiwan - Chi, Yu-Ho; Wu, Feng-Tzu; Ziebart, David A. (International journal of economic perspectives, 2025)
This study examines how rising food and energy prices, influenced by the Ukraine war and global instability, impact the dietary habits of Taiwanese consumers. Building on Grunert et al. (2023), which showed 81% of European consumers altered their food choices due to inflation, we explore whether Taiwanese consumers are becoming more price-conscious while prioritizing health and sustainability. Our findings indicate that taste remains a primary focus despite inflation, with increased attention to food quality, packaging, and local products, especially among women and younger consumers. This research offers valuable insights for food producers and retailers navigating contemporary consumer needs.